Analisis Indeks Kepuasan Pelanggan Perumda Tirtayasa Kota Pekalongan dengan menggunakan Important Performance Analysis - Choliq Sabana; Ari Muhardono; Mahirun Mahirun; Sigit Taruna; Danang Satrio; Mohamad Iqbal (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
Providing quality drinking water is the government's responsibility which is realized through the Regional Drinking Water Company (PDAM). The quality of PDAM services is a measure of success in meeting community needs. This research aims to determine the level of customer satisfaction with the service quality of Perumda Tirtayasa Pekalongan City. This type of research is quantitative descriptive research. The population in this research is customers of Perumda Tirtasaya, Pekalongan City in 2022 with a sample of 400 customers. The results of the research show that the Customer Satisfaction Index for Perumda Tirtayasa Pekalongan City services is 80.25, this means that the service performance of Perumda Tirtayasa Pekalongan City is perceived as "good" by the community. And the level of conformity/customer satisfaction with Perumda Tirtayasa Pekalongan City services is 92%.